TRANSFER OBJECTS USED IN THE PROCESSING OF COMPLEX EROSION - Alin NIOAȚĂ (Fiabilitate şi Durabilitate)
The construction and form of the transfer object depend on process parameters and influence the technological parameters and the state parameters of the process. The most frequently used form of transfer object is the disk form. In accordance with the type of operation we may use electrodes under the form of band and sometimes, very seldom, under the form of wire. The paper presents a transfer object under the form of stratified disk that allows the introduction of the working fluid through it..